Flow injection biamperometric determination of captopril - Palomeque, Miriam Edid (2002)
An automated method to determine captopril (1-[(2S)-3-mercapto-2-methylpropionyl]-L-proline) is proposed. A flow injection manifold based on the indirect biamperometric detection of the captopril by using Fe(III)/Fe(II) as an indicating redox system and a Z-shaped flow-cell configuration, was developed. The calibration curve is linear over the range 0.03-3.6 μg ml-1 of captopril. The relative standard deviation for the determination of 0.76 μg ml-1 of captopril is 0.97% (n=12) and the sample throughput is 69 h-1. This method was applied to the determination of captopril to commercially available pharmaceutical preparations.